2022
DOI: 10.3389/fpsyg.2022.828390
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Landscape of Problem-Based Learning Research (1981–2021)

Abstract: BackgroundProblem-Based Learning (PBL) is an instructional method of hands-on, active learning centered on investigating and resolving messy, real-world problems. This study aims to systematically analyze the current status and hotspots of PBL research and provide insights for research in the field.MethodsProblem-based learning-related publications were retrieved from the Web of Science Core Collection using “Problem-Based Learning”. Annual publications, countries, institutions, authors, journals, references, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Most of the articles were published between 2015 and 2022, with a noticeable increase in publishing beginning in 2005. This outcome is generally in line with the findings of the investigations carried out in the past (Karakus et al, 2019;Zhang et al, 2022). The Netherlands, Germany, and Turkey were the top three most productive countries with the Netherlands creating the most articles.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the articles were published between 2015 and 2022, with a noticeable increase in publishing beginning in 2005. This outcome is generally in line with the findings of the investigations carried out in the past (Karakus et al, 2019;Zhang et al, 2022). The Netherlands, Germany, and Turkey were the top three most productive countries with the Netherlands creating the most articles.…”
Section: Discussionsupporting
confidence: 87%
“…This study demonstrated that the MW-PBL-FC instructional model signi cantly improved learning outcomes in BMB courses and enhanced learning outcomes effectively. This is consistent with the ndings of similar studies conducted previously (Chen, Y., et al,2022;Zhang, F., et al,2022;Zhang, X., et al,2023;Qutob H.,2022;Li, Z., et al,2022;Gopalan C.,2019;. Obviously, the quality of the network, teacher-student interaction, and the instructor's power factor(Gopalan C.,2019) may also affect learning performance; however, this study does not address these variables and will be investigated in greater depth in future work.…”
Section: Comparison Of the Performance Of Mw-pbl-fc Teaching Model Im...supporting
confidence: 87%
“…Teachers and students can useWeChat to communicate instantly, answer questions, and share resources(Ma, R., et al,2023;Huang X.,2019) to compensate for the shortcomings of the MOOC.PBL is student-centered, which brings into play students' independence and active participation in learning, develops students' teamwork and communication skills, fosters critical thinking and the ability to analyze and solve problems, improves students' creative thinking skills, and promotes the integration of professional knowledge with clinical practice(Zhang, F., et al,2022;Zhang, X.,et al,2023) In addition, it exercises students' expression skills, develops students' clinical thinking, and improves students' teamwork skills(Zhang,X.,et al,2018;Zheng G,et al,2023;Wang Y. et al,2023;Zhang G.J.,2023; Zou H.,2022;Du W.,et al,2022,Zhang Y.F., et al,2022). However, PBL-centric approaches do not always allow students to grasp the key contents, or aid in the intervention, management, and assessment of teachers, etc.…”
mentioning
confidence: 99%
“…The rapid development of the educational environment has greatly affected medical education and traditional teaching models can no longer fully meet the medical students' learning needs 9 . PBL is a new trend in medical education in recent years, but there many obstacles and challenges that face the implementation of problem-based learning in many medical schools 10 . Practice is an effective learning pathway for improving clinical skills of medical students 11 .…”
Section: Discussionmentioning
confidence: 99%